Cargo Bike Sharing in Urban Areas: A Comparative Perspective on Different Types of Operators - Michael Bissel (Findings)
This study compares user demographics and user behavior of different types of cargo bike sharing operators in Berlin, Germany. Building on two survey datasets, the objective is to investigate similarities and differences with regard to the potential for sustainable mobility in urban areas. The findings suggest that both operator types can similarly contribute to car substitution while complementing each other in terms of user demographics and trip purposes.